The effects of orthodontic treatment on periodontal health among the orthodontic patients attending Kulliyyah Of Dentistry (KOD) IIUM specialist clinic - Witjaksono, Widowati; Hussin, Akbar Sham; SA Bakar, Sharifah Aishah; H Alias, Rahmah (2013)
Background: Orthodontic treatment requires remodeling of the periodontal tissues, including the periodontal ligament fibers and alveolar bone in order to straighten the misaligned teeth. The effect of orthodontic treatment is apparent esthetically but the effect to theperiodontal health is still in debate. Objective:To investigate the effect of orthodontic treatment on the periodontal condition among the orthodontic patients attending Kulliyyah of Dentistry (KOD), IIUM. Methodology: A quasi-experimental study was done among 11 patients scheduled for orthodontic treatment (sample group) at the Orthodontic Specialist Clinic, KOD. Those that fulfill the inclusion and exclusion criteria were selected; 11 patients who are waiting for orthodontic treatment were included as control (control group).The periodontal health of each patient was examined clinically using WHO 621 probe around the teeth and scored by using the Basic Periodontal Examination (BPE) method. The BPE readings were taken again 6 months after the beginning of orthodontic treatment.Baseline risk ratio(RR) before orthodontic treatment and that of six months after treatment were measured and compared. Results:The baseline RR between the sample group and the control group are: Sextant1 (S1): 0.562; Sextant2 (S2): 0.421; Sextant3 (S3): 2.250; Sextant4 (S4): 5.000; Sextant5 (S5): 3.600; Sextant6 (S6): 2.857. Conclusion: After 6 months of undergoing orthodontic treatment, there is no significant difference in the effect of orthodontic treatment on periodontal condition, except in Sextant 2.